2013
DOI: 10.1073/pnas.1309827110
|View full text |Cite
|
Sign up to set email alerts
|

Nonfunctional Na V 1.1 familial hemiplegic migraine mutant transformed into gain of function by partial rescue of folding defects

Abstract: Familial hemiplegic migraine (FHM) is a rare subtype of migraine with aura. Mutations causing FHM type 3 have been identified in SCN1A, the gene encoding the Na v 1.1 Na + channel, which is also a major target of epileptogenic mutations and is particularly important for the excitability of GABAergic neurons. However, functional studies of Na V 1.1 FHM mutations have generated controversial results. In particular, it has been shown that the Na V 1.1-L1649Q mutant is nonfunctional when expressed in a human cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
137
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(157 citation statements)
references
References 29 publications
15
137
4
Order By: Relevance
“…Strikingly similar phenotypes are exhibited by Na v 1.1 mutants linked to migraine (5)(6)(7)9). Of note, migraine mutations tend to cluster around Na v 1.1 VSDIV, lending further support to the utility of Hm1a for phenocopying FHM3.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…Strikingly similar phenotypes are exhibited by Na v 1.1 mutants linked to migraine (5)(6)(7)9). Of note, migraine mutations tend to cluster around Na v 1.1 VSDIV, lending further support to the utility of Hm1a for phenocopying FHM3.…”
Section: Resultsmentioning
confidence: 63%
“…Loss-of-function mutations in Na v 1.1 produce epilepsy syndromes, likely reflecting the critical importance of this Na v channel subtype in controlling the excitability of inhibitory interneurons in the brain (2)(3)(4). In contrast, gain-offunction mutations that diminish Na v 1.1 fast inactivation are linked to familial hemiplegic migraine type 3 (5)(6)(7)(8)(9). Therefore, Na v 1.1 has emerged as an important therapeutic target for brain disorders and, more recently, mechanical pain (10).…”
Section: Ica-121431mentioning
confidence: 99%
“…Trafficking-deficient mutant proteins have been shown to be rescued by lower temperature and molecular or pharmacological chaperones (Denning et al, 1992; Thomas et al, 2003; Varga et al, 2008; Guo et al, 2012; Saxena et al, 2012; Cestele et al, 2013). Here we found that decreased incubation temperature (30°C) increased surface and total levels of wildtype and mutant γ2L subunits.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism may generate phenotypic variability and also possibly be used in the development of therapeutic approaches. As recently shown for a missense SCN1A mutant identified in a family with pure familial hemiplegic migraine [43], rescue of folding defects may also transform nonfunctional loss-of-function mutants, an effect that is consistent with severe epilepsy, into gain-of-function ones, an effect that is consistent with familial hemiplegic migraine [44]. Animal models have confirmed that GEFS+ mutations cause loss of function of SCN1A and reduced excitability of GABAergic neurons [45].…”
Section: Generalized (Genetic) Epilepsy With Febrile Seizures Plusmentioning
confidence: 67%